Geographical and environmental contributions to genomic divergence in mangrove forests. (13th January 2021) - Da Silva, Michele Fernandes; Cruz, Mariana Vargas; Vidal Júnior, João De Deus; Zucchi, Maria Imaculada; Mori, Gustavo Maruyama; De Souza, Anete Pereira
Abstract: Assessing the relative importance of geographical and environmental factors to the spatial distribution of genetic variation can provide information about the processes that maintain genetic variation in natural populations. With a globally wide but very restricted habitat distribution, mangrove trees are a useful model for studies aiming to understand the contributions of these factors. Mangroves occur along the continent–ocean interface of tropical and subtropical latitudes, regions considered inhospitable to many other types of plants. Here, we used landscape genomics approaches to investigate the relative contributions of geographical and environmental variables to the genetic variation of two black mangrove species, Avicennia schaueriana and Avicennia germinans, along the South American coast. Using single nucleotide polymorphisms, our results revealed an important role of ocean currents and geographical distance in the gene flow of A. schaueriana and an isolation-by-environment pattern in the organization of the genetic diversity of A. germinans . Additionally, for A. germinans, we observed significant correlations between genetic variation with evidence of selection and the influence of precipitation regimens, solar radiation and temperature patterns. These discoveries expand our knowledge about the evolution of mangrove trees and provide important information to predict future responses of coastal species to the expected global changes during this century.